Menace to empire : anticolonial solidarities and the transpacific origins of the US security state - Jung, Moon-Ho, 1969- (American crossroads, 2022)
"Menace to Empire is a profoundly original and ambitious book, a history of race and empire that traces both the colonial violence and the anticolonial rage that the United States spread across the Pacific between the Philippine-American War and World War II. Author Moon-Ho Jung argues that the US national security state as we know it was born out of attempts to repress and silence colonized subjects, from the Philippines and Hawai'i to California and beyond, whose anticolonial aspirations challenged US claims to sovereignty. Jung examines how the contradictions of race, nation, and empire generated waves of revolutionary movements spanning the Pacific--anticolonial, antiracist, and labor movements that exposed and confronted the US empire. In response, the US state closely monitored and brutally suppressed those movements by racializing particular politics and distinct communities as seditious, exaggerating fears of pan-Asian solidarities and sowing anti-Asian racism under the guise of national security. Menace to Empire transforms familiar themes in American history to highlight the critical role of colonial violence in the formation of radical movements and the antiradical origins of anti-Asian racism. Radicalized by their opposition to the US empire and racialized as threats to US security, peoples in and from Asia pursued a revolutionary politics that gave rise to the national security state--the heart and soul of the US empire ever since"--